No ordinary rules. More on organizational behaviour: a discussion on forms and hibrydisms of post-bureaucratic organizations - Pierfranco Malizia (Revista de Psicologia)
The topics discussed in this contribution are founded on two basic assumptions; the first considers a complex organization as a social subsystem in which all the specific characteristics of the “macrosystem” may be found.  The second (consequential to the first) favours the interpretation of “organization-as-culture” (or as a sociocultural system). Assuming what has been said above, then, it follows (and this is the sense of this essay) that complex organizations, in as much as they are sociocultural (sub)systems, cannot be considered, perhaps today more than in the past, systems impervious to the sociocultural world of which they are a part, or in other words, it is not possible to speak of a culture of organizations as if it were a unique, coherent system of models and values: the plurality of cultural influences present in the highly differentiated contemporary societies is reflected also on the situations inside these organizations.